2005
DOI: 10.1192/bjp.187.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychotherapy in Alzheimer's disease

Abstract: There is no evidence to support the widespread introduction of brief psychotherapeutic approaches for those with Alzheimer's disease. However, the technique was acceptable and helpful individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
(30 reference statements)
0
57
0
1
Order By: Relevance
“…Four main areas were explored with each patient: autobiographical narrative; important past conflicts; impact of diagnosis, and improving interpersonal relationships, including the relationship with the partner. Burns et al (2005) did not find any significant difference in depression between treatment and control groups, nor did they find any change in the treatment group over pre-and postintervention. Nevertheless, caregivers (who had been involved in the sessions) demonstrated improved coping mechanisms and patients generally reported a positive experience in therapy.…”
Section: B R I E F P S Y C H O D Y N a M I C T H E R A P Ymentioning
confidence: 64%
See 1 more Smart Citation
“…Four main areas were explored with each patient: autobiographical narrative; important past conflicts; impact of diagnosis, and improving interpersonal relationships, including the relationship with the partner. Burns et al (2005) did not find any significant difference in depression between treatment and control groups, nor did they find any change in the treatment group over pre-and postintervention. Nevertheless, caregivers (who had been involved in the sessions) demonstrated improved coping mechanisms and patients generally reported a positive experience in therapy.…”
Section: B R I E F P S Y C H O D Y N a M I C T H E R A P Ymentioning
confidence: 64%
“…Burns et al (2005) conducted a randomized control trial with a sample of 40 patients with a diagnosis of MCI or early dementia to investigate the impact of brief psychodynamic therapy on mood, global wellbeing and cognition. Burns et al (2005) therapeutic approach was adapted for people with dementia via the use of home visits and involvement of the caregiver in the therapeutic sessions. Four main areas were explored with each patient: autobiographical narrative; important past conflicts; impact of diagnosis, and improving interpersonal relationships, including the relationship with the partner.…”
Section: B R I E F P S Y C H O D Y N a M I C T H E R A P Ymentioning
confidence: 99%
“…Some participants appeared to achieve a greater understanding as a result of this single experience of supportive listening, providing support for short-term therapies for some individuals (Burns et al, 2005). This study also suggests that medical/biological understandings of dementia may not be helpful.…”
Section: Discussionmentioning
confidence: 82%
“…Cheston et al (2003) evaluated six 10week psycho therapy groups for people with dementia and found significant improvement in scores for depression and marginal benefits in anxiety symptoms which were maintained at followup. Burns et al (2005) have shown that it is possible to apply randomised controlled trial methodology in assessing the impact of a psychotherapeutic approach in people with Alzheimer's disease. Although they found that brief psychotherapy (psychodynamic interpersonal therapy) did not improve scores on any of the key outcome measures, qualitative assessments reported trends towards a subjective benefit for both patients and carers.…”
Section: The Evidence Base For Psychotherapiesmentioning
confidence: 99%
“…as insight is often well preserved and psychological adjustment is difficult for individuals who assume that they face a future of inevitable decline (Burns et al, 2005). Denial is a common defence mechanism for patients and their relatives (Bahro et al, 1997).…”
Section: Psychotherapy In Dementia Carementioning
confidence: 99%